Experimental Study of a Pack of Supercapacitors Used in Electric Vehicles - Amari Mansour; Chabchoub Mohamed Hedi; Bacha Faouzi (The Scientific World Journal)
Electric vehicles have recently attracted research interest. An electric vehicle is composed of two energy sources, such as fuel cells and ultracapacitors, which are employed to provide, respectively, the steady-state and transient power demanded by the vehicle. A bidirectional DC-DC converter is needed to interface the ultracapacitor to a DC bus. The pack of ultracapacitor consists of many cells in series and possibly also in parallel. In this regard, this paper introduces a comparative study between two packs of supercapacitors. The first supercapacitor pack is composed of ten cells in series but the second supercapacitor pack is composed of five cells in series and two parallel circuits. Each cell is characterized by 2.5 V and 100 F. A number of practical tests are presented.